Talimogene Laherparepvec combined with anti-PD-1 based immunotherapy for unresectable stage III-IV melanoma: a case series. Issue 1 (16th May 2018) - Sun, Lillian; Funchain, Pauline; Song, Jung Min; Rayman, Patricia; Tannenbaum, Charles; Ko, Jennifer; Mcnamara, Michael; Marcela Diaz-Montero, C.; Gastman, Brian
Abstract : Background: Talimogene Laherparepvec (T-VEC) is an oncolytic virus approved as an intratumoral therapy for treating unresectable stage IIIB-IV metastatic melanoma. The mechanisms of action for T-VEC and checkpoint inhibitor are highly complementary. Recent studies have shown that combining checkpoint inhibitor therapy with T-VEC injection can lead to improved response rates for stage IIIB-IV melanoma patients. Methods: We reviewed 10 consecutive cases of stage IIIC to stage IVM1b melanoma patients that received T-VEC plus checkpoint inhibitor(s) therapy (pembrolizumab, ipilimumab/nivolumab, or nivolumab) treated between June 2016 and August 2017 at the Cleveland Clinic with a median follow-up of 7 months (range: 4 to 13 months). Responses of injected (on-target) and uninjected (off-target) lesions were evaluated according to RECIST 2.0. Results: The overall response rate for on-target lesions was 90%, with 6 patients experiencing a complete response in injected lesions. Two patients had off-target lesions, which were completely resolved after treatment. Blood samples were tested for 3 complete responders and 2 partial responders. CD4:CD8 ratio and frequencies of circulating PD1 + CD4 and CD8 T cells were elevated in complete responders but not partial responders. One patient died due to causes unrelated to melanoma and one patient died of progression of the disease. Conclusion: Our data suggest that combining checkpoint inhibitor(s) with T-VEC injection may provide a synergistic efficacy for patients with unresectable melanoma. We observed a better overall response rate and complete response rate compared to published studies on similar therapeutic regimens.